Early life risks and child development - Slemming, Wiedaad (My University, 2018)
Background Exposure to biological and psychosocial risks, particularly during the first three years of life, affects brain development and compromises the short- and long-term health and development of children, as well as their educational achievement and long-term productivity. This study sought to determine the effects of maternal and child environmental and psychosocial exposures during pregnancy and the first two years of the child’s life on growth and development outcomes in early childhood (up to 5 years) in an urban South African birth cohort. Methods Data used for this study was from the Birth to Twenty Plus (Bt20+) longitudinal birth cohort study, initiated in 1990 in the greater Johannesburg metropolitan area, South Africa. First, the associations between exposure to nine maternal risks, assessed in 1228 women, and subsequent infant birth weight was assessed. Second, the study examined the effects of risk exposure to the mother (and child) during pregnancy and the first year of a child’s life on stunting at age 2 years in 1098 mother–child pairs. Finally, the associations between ten demographic and psychosocial exposures occurring during the third trimester of pregnancy and the first two years of a child’s life and child development age 5 were examined in 636 mother-child pairs. Multivariable regression analyses were used to investigate associations between exposures and outcomes. Further analysis was undertaken to assess whether early life growth mediated the associations between maternal and household exposures and child development outcome at age 5. Results Unwanted pregnancy (or ambivalence) was associated with a ~156 g reduction in infant birth weight (β = −0.32, 95% confidence interval (CI): −0.51, −0.14). Tobacco use during pregnancy was negatively associated with BWZ (β = −0.32, 95% CI: −0.59, −0.05). Exposure to both these risks was associated with cumulative reductions in birth weight. Approximately 1 in 5 children were stunted at age 2 years, with males at greater risk than females. Higher maternal education was protective for females (adjusted odds ratio (AOR) = 0.35; 95% CI: 0.14, 0.87), while higher household SES was protective for males (AOR for richest SES group = 0.39; 95% CI: 0.16, 0.92). Males scored significantly lower than females on the developmental measure at age 5. Improved child developmental outcome was associated with higher birthweight for both sexes and superior linear growth in males. R-DPDQ scores increased by 0.84 units for every 1 SD increase in relative linear growth between birth and two years (β = 0.84 [95% CI 0.30, 1.39]). Socio-economic status (for both sexes) and maternal education for males were significant predictors of better child development. Growth status did not mediate the effects of socio-economic status (either sex) or maternal education (males) on developmental outcome. Conclusion Social factors, especially social determinants such as household SES and maternal education, were associated with early childhood growth and development in this context. Prenatal (using birthweight as a proxy) and postnatal growth were important for child development. Males were particularly vulnerable to poor growth and development in this cohort. The effects of household SES and maternal education on child development at 5 years were not mediated by linear growth between birth and 4 years.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa 2017.
Keywords: Child welfare; Child development--South Africa